The Making of Anti-Poverty Policies in Ghana Transnational Actors, Processes and Mechanisms - Foli, Rosina K. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book examines the roles played by transnational actors to influence poverty reduction policies in Ghana. Whereas previous studies on anti-poverty policies have primarily focused on the 'carrot and stick' approach deployed by transnational actors - whereby developmental assistance is granted in return of certain conditions being met - this book demonstrates that there are several alternative strategies. Indeed, rather than adopting 'hard' means of shaping policy, many transnational actors in fact use a 'soft' approach characterized by collaboration. In order to demonstrate this, the book examines two poverty reduction programmes. Utilising research based on interviews with national policymakers, civil-society organizations and the media, it compares different approaches used by transnational actors and the attendant outcomes for national and international parties. Drawing on an interdisciplinary perspective, the book will appeal to scholars and students of public policy and international relations. Rosina K. Foli is Senior Lecturer in the Department of Political Science, University of Ghana. Her research interests include social policy, governance, and poverty reduction in sub-Saharan Africa.
1 Transnational Actors and Policymaking in Sub-Saharan Africa: The Scholarly Context -- 2 Transnational Policy Process: Analytical Framework -- 3 Transnational Actors and Social Policymaking in Ghana: A Brief Historical Background -- 4 Transnational Actors and Policymaking: The Ghana Poverty Reduction Strategy (GPRS) -- 5 Ghana's Decision to LEAP Out of Poverty: Interrogating the Transnational Involvement -- 6 Transnational Policymaking After the GPRS and LEAP in Ghana and Beyond -- 7 Conclusion: Lessons and Implications.
Keywords: Political planning; Africa -- Politics and government; Political science; Public Policy; African Politics; Governance and Government